ISSUES ON THE DEVELOPMENT OF COLLISION METHOD OF LEGAL REGULATION OF FOREIGN LEGAL ENTITIES’ LIQUIDATION IN UZBEKISTAN - Azamat Ergashev (Scholar Express Journals, 2022)
The liquidation of enterprises in general is considered by a complex process, which is accompanied by the emergence of other significant legal relations between the State and the legal person. Moreover, the complication in the form of a foreign element causes the need for a structured collision-legal regulation both at the national and international levels. This article reveals the elements and specifics of the liquidation of foreign legal entities in the Republic of Uzbekistan and identifies a number of proposals to improve the conflict of laws regulation in the legislation. The author considers the opinions of jurists, provides statistics, as well as reveals foreign practice. The study conducted by the author in this work emphasizes the importance of applying precise mechanisms with regard to the procedures at the time of liquidation of a foreign legal entity, as well as after its termination. In conclusion, the author considers it advisable to make amendments to some provisions in the legislation related to this issue
Keywords: Conflict of laws; liquidation of a foreign legal entity; legal relationship; private law